EMOTIONAL INTELLIGENCE AS A MEDIATOR BETWEEN WORKPLACE BULLYING AND SELF-EFFICACY AMONG NURSES (The Research of Medical Science Review, 2024)
The study aims to explore the mediating role of emotional intelligence between workplace bullying and emotional intelligence among nurses. A purposive sample of 196 nurses, aged between 21 and 60 years, was collected from various government, semi-government, and private hospitals in Sialkot. The participants completed a self-developed demographic sheet alongside the Negative Act Questionnaire (NAQ-R), Wong and Law Emotional Intelligence Scale (WLEIS), and the General Self-Efficacy Scale (GSE). Results indicates that the indirect effect of workplace bullying on self-efficacy through emotional intelligence was significant (β =-.061, SE=.019, 95% CI [-. 099, -.026]). So, the overall model indicate that emotional intelligence fully mediates the effect of workplace bullying on self-efficacy. Findings suggest that workplace bullying acts as an adverse factor that has direct negative impact on emotional intelligence, but the ability of effective emotional identification and regulation can be a buffer zone for nurses for their self-efficacy.